CHILDREN’S LITERATURE AND ITS LITERARY PECULARITIES (IN THE WORKS OF LEWIS CARROLL) (Лучшие интеллектуальные исследования, 2025)
Abstract: This article explores the distinctive elements of children's literature as exemplified in the works of Lewis Carroll, particularly focusing on "Alice's Adventures in Wonderland" and "Through the Looking-Glass." It analyzes Carroll's innovative use of language, playful logic, and fantastical narratives that challenge conventional storytelling. The article delves into themes of identity, absurdity, and the fluidity of reality, highlighting how Carroll's imaginative style resonates with the curiosity and perceptions of children. Additionally, it discusses the cultural and historical context of Carroll’s writing, noting how his background influenced his literary approach. The exploration of illustrations and their integration into the text is also examined, enhancing the understanding of Carroll's impact on modern children's literature. Overall, the article posits that Carroll's unique literary techniques not only engage young readers but also invite adult interpretations, solidifying his place as a pivotal figure in the realm of children's literature.Аннотатция: В этой статье рассматриваются отличительные элементы детской литературы, представленные в произведениях Льюиса Кэрролла, в частности, «Приключения Алисы в Стране чудес» и «Сквозь зеркало». В статье анализируется новаторское использование Кэрроллом языка, игровой логики и фантастических повествований, которые бросают вызов традиционному повествованию. Статья углубляется в темы идентичности, абсурда и текучести реальности, подчеркивая, как творческий стиль Кэрролла резонирует с любопытством и восприятием детей. Кроме того, в ней обсуждается культурный и исторический контекст творчества Кэрролла, отмечается, как его происхождение повлияло на его литературный подход. Также рассматривается исследование иллюстраций и их интеграция в текст, что улучшает понимание влияния Кэрролла на современную детскую литературу.  В целом, в статье утверждается, что уникальные литературные приемы Кэрролла не только привлекают молодых читателей, но и приглашают взрослых к интерпретациям, укрепляя его место как ключевой фигуры в сфере детской литературы.